2012
DOI: 10.1155/2012/608013
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Determinants of Dementia in Patients with Mild Cognitive Impairment and Brain Subcortical Vascular Changes: A Study of Clinical, Neuroimaging, and Biological Markers—The VMCI-Tuscany Study: Rationale, Design, and Methodology

Abstract: Dementia is one of the most disabling conditions. Alzheimer's disease and vascular dementia (VaD) are the most frequent causes. Subcortical VaD is consequent to deep-brain small vessel disease (SVD) and is the most frequent form of VaD. Its pathological hallmarks are ischemic white matter changes and lacunar infarcts. Degenerative and vascular changes often coexist, but mechanisms of interaction are incompletely understood. The term mild cognitive impairment defines a transitional state between normal ageing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…The vascular MCI (VMCI)-Tuscany study is an ongoing multicenter, prospective, observational study aimed at evaluating predictors of the transition from VMCI (defined by the presence of moderate-to-severe white matter lesions) to dementia [12]. The study methodology has been reported elsewhere [12].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vascular MCI (VMCI)-Tuscany study is an ongoing multicenter, prospective, observational study aimed at evaluating predictors of the transition from VMCI (defined by the presence of moderate-to-severe white matter lesions) to dementia [12]. The study methodology has been reported elsewhere [12].…”
Section: Methodsmentioning
confidence: 99%
“…The study methodology has been reported elsewhere [12]. To be included, outpatients, referred from neurologic or geriatric units, had to be classified as affected by MCI with SVD according to the following inclusion criteria: (1) MCI defined according to Winblad et al's criteria [3] and (2) evidence on magnetic resonance imaging (MRI) of moderate-to-severe degrees of white matter hyperintensities (WMH) according to the modified version of the Fazekas scale [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach characterizes the Vascular Mild Cognitive Impairment Tuscany Study. 66 In clinical-pathologic studies, the prevalence rate of MixD is highly variable between 2% and 60% 8 indicating lack of clarifying knowledge about the relationship between vascular lesions, neurodegeneration, and the clinical manifestations. Almost 1/3 of the included patients exhibited mild dementia at baseline, where 42% had AD, 21% MixD, and 14% SVD.…”
Section: Discussionmentioning
confidence: 99%
“…The VMCI-Tuscany study is a multicenter, prospective, observational study aimed at evaluating predictors of the transition from MCI with SVD to dementia [23]. The outpatient VAS-COG clinic is entirely dedicated to assess and follow-up patients affected by cognitive, psychiatric, and behavioral disturbances caused or associated with cerebrovascular diseases, and it is active since January 2006 [24].…”
Section: Recruitment Proceduresmentioning
confidence: 99%